Usability evaluation of web-based dietary application MyProteinGuideTM among caregivers of children with disorders of amino acid metabolism (AAMDs) - Ying, Lim Jing; Rajikan, Roslee; Ali, Mohamad Nazlena; Amit, Noh; Hamid, Haslina Abdul; Yin, Leong Huey; Mohamad, Maslina; Qi, Koh Bi (Universiti Putra Malaysia Press, 2024)
Introduction: Dietary intervention is the cornerstone in the management of disorders of amino acid metabolism (AAMDs). Therefore, a MyProteinGuideTM web-based application was developed to assist the caregivers of AAMDs in self-monitoring their nutritional status especially the dietary intake. Materials and methods: A cross-sectional study was conducted to evaluate the usability of the MyProteinGuideTM web-based application among caregivers of patients diagnosed with AAMDs including aminoacidopathies (AA), Organic Aciduria (OA) and Urea Cycle Disorders (UCD) aged between 6 months to 18-year-old who are receiving treatment in the genetic clinic, Hospital Kuala Lumpur (HKL) and Hospital Pulau Pinang (HPP). A total of 30 caregivers participated in this study, out of most of the caregivers had children with AA (43.3%), followed by OA (30.0%) and UCD (26.7%). The Malay version of mHealth application usability questionnaire (MAUQ) and System Usability Scale (SUS) were used as the assessment tools to assess the application usability. Results: An overall usability mean (SD) score of 5.88 (0.76) out of a maximum score of seven as rated by MAUQ while SUS score was 78.17 (15.70), indicating good usability. In term of domain breakdown, the highest scoring domain being Domain 3: Usefulness 5.99 (0.79) followed by Domain 2: User Interface and Satisfaction 5.94 (0.73) and Domain 1: Ease of Use 5.69 (0.91). Suggestions to improve the application include to make it into a responsive web application or mobile application which are user-friendly to both mobile phone user. Conclusion: In conclusion, the usability results showed that MyProteinGuideTM had a good usability.